PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, BUDAYA KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI BANK - Ivan Fadilla Hadi; Puja Mustika (Yayasan Nusantara Hasana Berdikari, 2023)
Employee performance has a role in maintaining organizational effectiveness so that it excels in the world of existing business competition. This study aims to analyze those that affect employee performance including Work Discipline (X1), Work Motivation (X2), Work Culture (X3), Work Environment (X4) and Employee Performance (Y1). The method used is a quantitative method by distributing questionnaires to 100 respondents to the Bank's employees. From this study it can be concluded that work discipline has a positive effect on employee performance, work motivation has a positive effect on employee performance, work culture has no significant effect on employee performance, and work environment has no positive effect on employee performance.